(untitled) (Scientific journal of the Fergana State University, 2024)
This article expresses an opinion about the 4K model, which is the driving force behind the development of the state, teaching the necessary skills to a student of the 21st century. Information is presented on the formation of 4K activity among schoolchildren and students in the modern educational process. Changes in the existing content and methods of training future primary school teachers in a higher educational institution are discussed based on new requirements, as well as approaches aimed at developing competence in the 4K conditions of teacher and student. The study also pays special attention to the educational process and highlights various cases. A step-by-step guide will be provided for a deeper understanding of the 4K method. In this case, primary school teachers should be confronted with the importance of taking into account the cognitive abilities and interests of students, the formation of skills based on the principles of learning, when organizing the process of teaching subjects according to the 4K method. It is very important for future primary school teachers to take into account the cognitive abilities and interests of students and develop skills based on educational principles when organizing the process of teaching pedagogy based on 4K methods. It also describes how these processes are explained and addressed through pedagogical competence.